1992
DOI: 10.1002/app.1992.070450708
|View full text |Cite
|
Sign up to set email alerts
|

An XPS study of the surface–bulk compositional differences in siloxane‐containing block copolymers and polymer blends

Abstract: SYNOPSISX-ray photoelectron spectroscopy (XPS) is used to compare the surface behavior in various binary systems of poly (dimethylsiloxane) with poly( bisphenol A sulfone) and poly-(bisphenol A carbonate). All the systems studied show a pronounced surface enrichment in siloxane. At a fixed siloxane concentration in the bulk the lowest extent of surface enrichment is observed in the neat copolymers, next go the blends of copolymers in homopolymers, and the highest extent of surface enrichment is characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 6 publications
1
33
0
3
Order By: Relevance
“…He suggested that the differences in the surface free energy of various components within a polymer membrane may dominate the overall surface morphology, whereby the lower surface energy segment resided near the polymer-air interface [16,17,[48][49][50].…”
Section: Surface Behavior Of Copolymer Speek-hq Membranementioning
confidence: 99%
“…He suggested that the differences in the surface free energy of various components within a polymer membrane may dominate the overall surface morphology, whereby the lower surface energy segment resided near the polymer-air interface [16,17,[48][49][50].…”
Section: Surface Behavior Of Copolymer Speek-hq Membranementioning
confidence: 99%
“…6 The quantitative surface analysis of the PPO-PS decreases substantially with increasing MW of the siloxane additive. In 1% blends, for example, blends was made based on the resolution of the Cls spectra into contributions due to the ether the coverage of the blend surface with siloxane drops from about 100 to 50% when the PDMS carbon atom of PPO (E b Å 286.6 eV) and all other carbon atoms (E b Å 285.0 eV).…”
Section: Introductionmentioning
confidence: 99%
“…Herein the sol-gel method allows diffusion limitations to be avoided, inevitable, when bulky dendrimer or dendron is anchored to the surface of ready carrier [64][65][66][67][68][69]. The materials obtained were characterized by infrared spectroscopy (IR), X-ray photoelectron spectroscopy (XPS) and solid-state nuclear magnetic resonance (NMR) spectroscopy, that confirmed the presence in their structures of fragments, inherent in the SiO 2 bulk support [74,75] [76][77][78][79][80].…”
Section: The Synthesis Of Heterogeneous Dendrimer-based Catalystsmentioning
confidence: 99%
“…Microporous dendr-G3-SiO2 (Figure 2 The materials obtained were characterized by infrared spectroscopy (IR), X-ray photoelectron spectroscopy (XPS) and solid-state nuclear magnetic resonance (NMR) spectroscopy, that confirmed the presence in their structures of fragments, inherent in the SiO2 bulk support [74,75], PPI dendrimers (NCH2CH2CH2N, NCH2CH2CH2NH2, etc.) [76] and modifying groups, that link the former two residues, include epoxide-opening products of the former glycidyl groups (SiCH2CH2CH2O, OCH2CH(OH)CH2NH) [76][77][78][79][80].…”
Section: The Synthesis Of Heterogeneous Dendrimer-based Catalystsmentioning
confidence: 99%